ONLINE TRADING ON TELEGRAM: LINGUISTIC FINTECH STUDY - Suryani, Yunita; Yulianto, Bambang; Suhartono (Proceedings of International Conference on Islamic Civilization and Humanities, 2024)
Fintech (financial technology) is a financial service through an application system or digital platform with a quick and easy response. The focus of research on this linguistic study of fintech is the persuasive language used in marketing fintech products. One of the persuasive characteristics of the fintech industry on telegram social media when offering products is to influence account group members to become investors in their products. The purpose of this study is to describe the persuasive speech performed by the fintech industry on telegram social media accounts. The method in this research is descriptive qualitative with netnography approach. Data collection techniques use orthographic pairing. Furthermore, data analysis techniques use triangulation. The results of this study obtained data on rational persuasive speech and persuasive suggestions made by the fintech industry on telegram social media with the findings of investment fraud committed by several fintech industries in telegram social media accounts using language as the medium.